REVEALING SOCIAL CONFLICT AS SEEN IN THE DRAMA THE MERCHANT OF VENICE BY WILLIAM SHAKESPEARE - Firdiansyah, Firdiansyah; Al Amin; Mutiara Indah Lestari (English Language, Linguistics, Literature, And Education Journal, 2024)
This article discusses the social conflicts as seen in The Drama The Merchant Of Venice By William Shakespeare. This research was conducted to help readers identify and understand the social conflicts contained in the drama’s script. The main purpose of this research is to identify anf find out; 1) To identify the causes of Social conflict as seen in the drama The Merchant of Venice by William Shakespeare. 2) To find out the impacts of Social conflict as seen in the drama The Merchant of Venice by William Shakespeare. The design of this research is descriptive qualitative, the writer uses theory to analyze the data, the theory from Soekanto (1990) then uses Sociological approach. In collecting data, the writer uses documentation technique and uses content analysis. The results of this study are; First, 5 social problem causes social conflict in this drama, including crime, family disoganization, violation of social norms, demographic issues, bureaucracy. Second, 3 impacts of social conflict, including increased in-group solidarity, disintegration and breakdown of the group's unity, changes in the personality of individuals.